Importance of Corporate Social Responsibility Strategies in Malaysian Companies - Dinara, Assanova (2013)
Corporate social responsibility (CSR) concept has evolved over the time from being relatively insignificant to a concept that has been actively implemented by organizations. The reason why many organizations implement CSR strategies is because of the various benefits which CSR is capable of providing. In Malaysia, the practice of CSR is growing fast and the government has taken steps to make CSR reporting a part of the corporate governance requirements of public listed companies. No doubt, there is an increasing number of Malaysian companies are implementing CSR as they seem to realize the importance of using CSR strategies to enhance their competitiveness and long term profitability. In fact, there are still a large number of companies which have yet embrace CSR strategies because companies like these do not know about potential benefits from using CSR strategies. In essence, these companies do not implement proper CSR strategies because they feel it is not an effective way to attract customers. Hence, this research is being carried out to show how Malaysian companies are implementing CSR and how they have been benefited. The analysis is carried by using Malaysian property development companies to have an idea on how CSR strategies benefited them in enhancing the competitiveness of their industry and the Malaysia economy. The study would be exploratory in nature and utilize qualitative research methods comprising of interviews and content analysis. There will be an interview carried out with a leading Malaysian property developer in order to acquire insights about the use of CSR strategies and how it helps enhance their competitiveness etc. it will be determined whether CSR strategies used by companies would help them acquire long term profitability for shareholders.